2018
DOI: 10.1002/oby.22143
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Physical Training Improves Weight Loss After Roux‐en‐Y Gastric Bypass Surgery: A Randomized Controlled Trial

Abstract: Physical training following RYGB improves weight loss and cardiovascular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
0
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(133 citation statements)
references
References 41 publications
8
107
0
17
Order By: Relevance
“…Four interventions (n = 6 publications) delivered lifestyle and nutrition counselling‐focused MDT support, four interventions (n = 7 publications) delivered psychology‐focused MDT support, and 10 interventions (n = 21 publications) delivered exercise‐focused MDT support (Table ). There were five interventions delivered preoperatively, 10 post‐operatively, and three preoperatively and post‐operatively (Table ; detailed characteristics in Table S2). Of the post‐operative interventions, seven were concluded within the first 6‐month post‐operative, and six extended beyond or commenced after 6‐month post‐operative …”
Section: Resultsmentioning
confidence: 99%
“…Four interventions (n = 6 publications) delivered lifestyle and nutrition counselling‐focused MDT support, four interventions (n = 7 publications) delivered psychology‐focused MDT support, and 10 interventions (n = 21 publications) delivered exercise‐focused MDT support (Table ). There were five interventions delivered preoperatively, 10 post‐operatively, and three preoperatively and post‐operatively (Table ; detailed characteristics in Table S2). Of the post‐operative interventions, seven were concluded within the first 6‐month post‐operative, and six extended beyond or commenced after 6‐month post‐operative …”
Section: Resultsmentioning
confidence: 99%
“…The eight included trials 17 28–34 were published from 2011 to 2018 and performed in the USA, 28 30–33 England, 29 Iran 17 and Denmark. 34 All of the studies focused on patients who underwent roux-en-Y gastric bypass, 17 28–34 gastric banding, 29 31 32 sleeve gastric 17 29 31 or lap band 31 bariatric surgery. The included studies reported data on 347 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The present sub‐study is part of a larger study investigating the effects of supervised physical training following RYGB on weight loss, 24 muscle strength and aerobic capacity, 26 physical activity and quality of life 27 and markers of CVD 17,25 . Results reported in this paper are based on secondary outcome variables and only include samples before and 6 months after bariatric surgery, that is, relatively early after bariatric surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The study design has been described in detail elsewhere 24 . In the present study, we included 42 women and 18 men, mean age 42.3 years, who were eligible for RYGB according to the national and international guidelines, as well as Danish criteria regulating free access to bariatric surgery (body mass index [BMI] > 35 kg/m 2 with obesity‐related disease or BMI > 50 kg/m 2 with obesity‐related social or physical complications).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation